Bathymetric distribution and recruitment of the spider crab Libinia spinosa H. Milne Edwards 1834 in the Ubatuba and Caraguatatuba regions, northern coast of São Paulo, Brazil (Crustacea, Brachyura, Majoidea, Pisidae) - Braga, Adriane A. [UNESP]; Fransozo, Adilson [UNESP]; Bertini, Giovana [UNESP]; Fumis, Patricia B. [UNESP] (My University, 2007)
The objective of this study was to investigate the spatial and temporal distribution of Libinia spinosa H. MILNE EDWARDS 1834 on unconsolidated sublittoral bottoms in two regions off the northern coast of the state of São Paulo, and to analyze the influence of environmental factors on the occurrence of this species and observe the recruitment pattern of its young. Crabs were collected monthly (July 2001 through June 2003) at depths of 5, 10, 15, 20, 25, 30 and 35 In, from a fishing boat equipped with two double-rig nets. Samples of water and sediment were collected for analysis of environmental factors. A total of 2112 spider crabs was obtained (701 juveniles and 1411 adults). The highest abundance was observed at depths of 20 and 25 m, in both regions. These localities were characterized by substrate composed of very fine sand and silt-clay. In regard to the temporal distribution, juveniles and adults predominated in the summer and winter months respectively. From these results, one can infer that the distribution of L. spinosa is related to environmental factors favorable for its life cycle; sediment type is the factor which most strongly determines its presence. © E. Schweizerbart'sche Verlagsbuchhandlung (Nägele u. Obermiller), 2007.
Keywords: Environmental factors; Habitat preference; Juveniles; Spatial and temporal distribution; abundance; crab; environmental factor; geographical distribution; habitat selection; intertidal environment; recruitment; spatiotemporal analysis; species occurrence; Brazil; Caraguatatuba; Sao Paulo [Brazil]; South America; Ubatuba; Araneae; Brachyura; Crustacea; Decapoda (Crustacea); Libinia spinosa; Majidae; Majoidea; Pisidae